Potencial de óleos essenciais de plantas medicinais no controle de fitopatógenos - Fonseca, Maira Christina Marques; Lehner, Miller da Silva; Gonçalves, M. G.; Paula Júnior, Trazilbo José de; Silva, A. F.; Bonfim, Filipe Pereira Giardini [UNESP]; Prado, A. L. (FapUNIFESP (SciELO), 2015)
In addition to their value as therapeutic resources, medicinal plants also have the potential to be used as a source of alternative compounds against plant pathogens. The objective of this study was to evaluate the effect of essential oils extracted from the medicinal species Baccharis dracunculifolia, Schinus terebinthifolius and Porophyllum ruderale on the growth of the fungal plant pathogens Fusarium oxysporum f. sp. phaseoli (Fop), F. solani f. sp. phaseoli (Fsp), Sclerotinia sclerotiorum (Ss), S. minor (Sm), Rhizoctonia solani (Rs), Sclerotium rolfsii (Sr) and Macrophomina phaseolina (Mp). The radial mycelial growth of the fungi was evaluated on potato dextrose agar (PDA) in Petri dishes with five concentrations (0, 250, 500, 1000 and 3000 µL L-1) of the essential oils. Mycelial discs (5 mm diameter) of the growing colonies of each fungus were transferred to Petri dishes, which were maintained at 23 °C in the dark for 48 hours. The essential oil of B. dracunculifolia was the most effective oil in the reduction of the mycelial growth of all fungi. It completely inhibited their growth at 3000 mg L-1. At 250 mg L-1, the growth reduction caused by the oil of B. dracunculifolia varied from 29% (Fs) to 80% (Rs); at 500 mg L-1, it varied from 29% (Fs) to 98% (Sr); and at 1000 mg L-1, it varied from 41% (Fs) to 100% (Sr). The reduction of the mycelial growth caused by the oil of S. terebinthifolius at 3000 mg L-1 varied from 27% (Fsp) to 74% (Rs). At this concentration, the oil of P. ruderale reduced the mycelial growth of Ss by 72%, of Rs by 80% and of Mp by 82%, without significant effects on the mycelial growth of Fsp and Fop. We conclude that the essential oils of B. dracunculifolia, S. terebinthifolius and P. ruderale have the potential to be used to control the plant pathogens tested, especially the oil of B. dracunculifolia.

Além do valor como recurso terapêutico, plantas medicinais também possuem potencial para serem utilizadas como fonte de princípios ativos contra fitopatógenos. O objetivo deste trabalho foi avaliar o efeito de óleos essenciais das espécies medicinais Baccharis dracunculifolia (alecrim-do-campo), Schinus terebinthifolius (aroeirinha) e Porophyllum ruderale (arnica-brasileira) sobre o crescimento dos fungos fitopatogênicos Fusarium oxysporum f. sp. phaseoli (Fop), F. solani f. sp. phaseoli (Fsp), Sclerotinia sclerotiorum (Ss), S. minor (Sm), Rhizoctonia solani (Rs), Sclerotium rolfsii (Sr) e Macrophomina phaseolina (Mp). Avaliou-se em placas de Petri o crescimento radial desses fungos em meio batata-dextrose-ágar (BDA) com cinco concentrações (0, 250, 500, 1000 e 3000 mg L-1) dos óleos essenciais. Discos de micélio (5 mm de diâmetro) de cada fungo em crescimento foram transferidos para placas de Petri que foram mantidas a 23°C no escuro por 48 horas. O óleo essencial de alecrim-do-campo foi o mais eficiente na redução do crescimento micelial de todos os fungos, com inibição completa quando se utilizou a concentração de 3000 mg L-1. A redução de crescimento variou de 29% (Fs) a 80% (Rs) a 250 mg L-1 do óleo essencial de alecrim-do-campo; a 500 mg L-1, variou de 29% (Fs) a 98% (Sr); e a 1000 mg L-1, de 41% (Fs) a 100% (Sr). A redução do crescimento dos fungos pelo óleo de aroeirinha na concentração de 3000 mg L-1 variou de 27% (Fsp) a 74% (Rs). Nessa concentração, o óleo de arnica-brasileira reduziu o crecimento micelial de Ss em 72%, o de Rs em 80% e o de Mp em 82%, sem efeitos significativos sobre o crescimento micelial de Fsp e Fop. Conclui-se que os óleos essenciais de alecrim-do-campo, aroeirinha e arnica-brasileira possuem potencial para o controle dos fungos fitopatogênicos estudados, com destaque para o óleo de alecrim-do-campo.
Potential of essential oils from medicinal plants to control plant pathogens
Keywords: Alternative control; Baccharis dracunculifolia; Schinus terebinthifolius; Porophyllum ruderale; Controle alternativo; Alecrim-do-campo; Aroeirinha; Arnica-brasileira